Comparative analysis of the national law of Latvia and Germany in regard to AML/CTF: a threat of reputational risks as a driver of strengthening of control over the financial sector - Mežale, Anna (Riga Graduate School of Law, 2021)
The thesis aims to analyse the nature of differences between the national law of Latvia and Germany in regard to anti-money laundering with respect to the financial sector, as well as the correlation between current national law and the development of the anti-money laundering and counter-terrorism financing systems of Latvia in Germany with profiles of both countries by using a qualitative comparative interdisciplinary method. As such, to provide an analysis of the national law of Latvia and Germany, three particularly important aspects of the anti-money laundering system in regard to the financial sector have been selected – risk-based approach, identification and criminalization. To achieve this aim, an analysis of the concepts at international and European Union is provided, as well as the current national law of Latvia in Germany in regard to these concepts. To determine a link between the current national law and the development of anti-money laundering systems of both countries, an analysis of profiles of both countries and events surrounding the development of anti-money systems of both countries are analysed, where the author reaches the conclusion, that existing differences between Latvian and German law are present in connection to the most vulnerable fields of the financial sectors of both countries
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law::Commercial and company law; Money laundering; Latvia; Germany